2.ETHNOMEDICINE AND MAGICO-RELIGIOUS BELIEFS OF THE KONDH TRIBE IN BOUDH DISTRICT OF ODISHA_ INDIA By C. R. SAHU1_ R. K. NAYAK2 AND N. K. DHAL3 - R. K. NAYAK AND N. K. DHAL, C. R. SAHU (LIFE SCIENCES LEAFLETS, 2013)
Odisha in the eastern part of India is very rich in plant biodiversity as well as in ethnic diversity and has a great traditional knowledge base in plant resources. It has the third largest concentration of tribes forming about 23% of total population and they lead an intricate life totally dependent on forest plants. The Kondhs are major tribal community in the Boudh district and its adjoining regions. They have a rich tradition of religion and culture. Their religious practices and beliefs are based on super naturalism. A study of the plants related to magico-religious beliefs in Kondh dominated regions revealed the use of 48 plants belonging to 34 families. All plant species are used both in magico-religious purpose as well as in the treatment of different ailments. Details of the uses of plants and conservational practices employed by the tribes are provided. KEY WORD: Ethnomedicine, Magico-religious, Kondh, Boudh, Odisha.